Hunting for Neighboring Open Clusters with Gaia DR3: 101 New Open Clusters within 500 pc - Qin, Songmei; Zhong, Jing; Tang, Tong; Chen, Li (The Astrophysical journal. Supplement series, 2023)
We systematically searched for open clusters in the solar neighborhood within 500 pc using the pyUPMASK and HDBSCAN clustering algorithms based on Gaia DR3. Taking into consideration that the physical size for most open clusters is less than 50 pc, we adopted a slicing approach for different distance shells and identified 324 neighboring open clusters, including 223 reported open clusters and 101 newly discovered open clusters, named here as the Open Cluster of Solar Neighborhood. Our discovery has increased the number of open clusters in the solar neighborhood by about 45%. In this work, larger spatial extents and more member stars were attained for our cluster sample. We provided the member stars and the membership probabilities through the pyUPMASK algorithm for each cluster and derived their astrophysical, age, and structural parameters.